(untitled) (Taqdir, 2025)
This study aims to describe various factors that cause difficulties for female students in using Arabic vocabulary at Ma’had Jami’ah, State Islamic University of North Sumatra Medan. The method applied is a descriptive qualitative approach with data collection through observation, in-depth interviews, and documentation studies. The subjects of the study consisted of five female students from the PGMI, Management, and PAI departments who experienced obstacles in applying Arabic vocabulary. The findings of the study indicate two main groups of factors, namely internal factors and external factors. Internal factors include low interest and motivation in learning, limitations in vocabulary mastery and difficulty in understanding the material, lack of self-confidence accompanied by anxiety when speaking, and varying educational backgrounds. Meanwhile, external factors include less diverse teaching methods, limited learning resources, and minimal learning time and opportunities to interact using Arabic in the ma’had environment. These results emphasize the importance of implementing a more innovative and comprehensive learning approach to improve the mastery of Arabic vocabulary for female students in the Ma’had Jami’ah environment.